2014
DOI: 10.1248/bpb.b14-00098
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Triterpenoid Saponin-Rich <i>Adisia gigantifolia</i> Extract on Human Breast Adenocarcinoma Cells <i>in Vitro</i> and <i>in Vivo</i>

Abstract: The aim of this study was to explore whether the ethanolic extract of Ardisia gigantifolia rhizomes (AGB-5), a traditional herbal medicine from China, could affect the proliferation of human breast adenocarcinoma (MCF-7) cells in vitro and to explore the antitumor effects of AGB-5 in BALB/c mice engrafted with MCF-7 cells. The results showed that AGB-5 markedly inhibited the proliferation of MCF-7 cells with an IC 50 value of 11.89 1.12 µg/mL, increased the S phase and decreased the G2/M phase without influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…**p < 0.01 compared with negative control, *p < 0.05 compared with negative control NSCLC. Numerous experiments confirmed that active ingredient from natural products such as triterpenoids, alkaloids, polysaccharides, saponins, and other active substances could be used to treat malignant tumors and reduce the side effects of chemotherapy (22,23,24,25). Additionally, various studies recently reported that anthocyanins could inhibit cellular transformation and cell-cycle progression, and induced apoptosis in different human cell lines (13,26,27,28).…”
Section: Discussionmentioning
confidence: 97%
“…**p < 0.01 compared with negative control, *p < 0.05 compared with negative control NSCLC. Numerous experiments confirmed that active ingredient from natural products such as triterpenoids, alkaloids, polysaccharides, saponins, and other active substances could be used to treat malignant tumors and reduce the side effects of chemotherapy (22,23,24,25). Additionally, various studies recently reported that anthocyanins could inhibit cellular transformation and cell-cycle progression, and induced apoptosis in different human cell lines (13,26,27,28).…”
Section: Discussionmentioning
confidence: 97%